Dysmenorrhea and Menorrhagia A Clinician's Guide - Smith, Roger P. (Springer International Publishing, 2018)
Dysmenorrhea is estimated to effect upwards of 70% of women during their lifetime and "heavy menstrual periods" is one of the most frequently given reasons for hysterectomy in the United States. Despite the dramatic growth of dysmenorrhea treatment with non-steroidal anti-inflammatory agents (NSADs) in the 1980s, young women continue to go undiagnosed and under treated. The diagnosis and management of heavy menstrual bleeding has even poorer general understanding because of its more complicated etiologies. With a working knowledge of the underlying pathophysiology, all clinicians should be able to establish both the diagnosis and a credible treatment plan that will result in a significant chance of clinical improvement for most patients. This book addresses the pathophysiologic underpinnings of both dysmenorrhea and menorrhagia and provides clinicians with practical approaches to establishing the diagnosis, proven tactics for successful therapeutic interventions and dealing with the challenging atypical case, and effective patient counseling. It teaches principles, including the role prostaglandins play in both conditions, as well as procedures, like surgical options and TENS, providing a balance of the practical and the esoteric. The inclusion of patient education and counseling materials additionally increases its usefulness for the busy clinician. This is an ideal guide for ob/gyn clinicians, residents, and trainees caring for patients with these common, but often misunderstood diseases. .